Bioactive components in milk and dairy products - Majid, Sumaiya (SLU/Dept. of Food Science, 2016)
Milk is a complex liquid that has expanded its more conventional role and is more than a source of nutrients for young mammals. In the last few decades, a great deal of research has shown that milk and dairy products provide a broad range of bioactive components. Bioactive components can be defined as components in foods that have a physiological function. The aim of this study was to give a general overview on bioactive components found in milk and dairy products and what valuable health effects they might have. Milk consists of a mixture of components but the main components are water, lactose, fat, proteins and minerals. The composition of milk can differ and are influenced by number of dissimilar factors. In this thesis calcium, specific bioactive proteins (lactorferrin, α-lactalalbumin, β-lactoglobulin, glycomacropeptide, and immunoglobulin) oligosaccharides and conjugated linoleic acid will be overviewed. However, these components are just a small fraction of all bioactive components found in milk and dairy products. Some of them are natural milk components, others emerge during digestive processes or fermentation processes in dairy products. Numerous of health effects of these bioactive components have been described in in vitro studies, animal trials, a small number of epidemiological studies and human clinical trials. The studies show that these bioactive components exhibit antimicrobial effect, anticarcinogenic properties, ACE-inhibitory activity, anti-hypertension properties, effects on the cholesterol levels etc. Although bioactive components in milk and dairy products is a well studied area there is a lack of human clinical trials and epidemiological studies to draw conclusions regarding health benefits in humans. However, the development of functional foods with health properties is a market that is expanding and will continue to do so in the coming future. Through the knowledge and understanding of how these components function, new health promoted products can be developed.